2007
DOI: 10.1007/s11064-006-9246-0
|View full text |Cite
|
Sign up to set email alerts
|

Salsolinol, an Endogenous Neurotoxin, Activates JNK and NF-κB Signaling Pathways in Human Neuroblastoma Cells

Abstract: Salsolinol, an endogenous neurotoxin, is known to be involved in the pathogenesis of Parkinson's disease (PD). In the present study, we have investigated the effects of salsolinol on the activation of two different signaling pathways that involve c-Jun N-terminal kinase (JNK), and nuclear factor-kappaB, (NF-kappaB) in human dopaminergic neuroblastoma SH-SY5Y cells. Salsolinol treatment caused upregulation in the levels of c-Jun and phosphorylated c-Jun. It also caused degradation of IkappaBalpha and translocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Glycolysis is a crucial process in DM and the most extensively investigated metabolic pathway (22). MG is an important byproduct in this pathway and its production is increased due to hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Glycolysis is a crucial process in DM and the most extensively investigated metabolic pathway (22). MG is an important byproduct in this pathway and its production is increased due to hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…ROS were increased and glutathione levels were decreased when SH-SY5Y cells were treated with racemic salsolinol, especially at concentrations near to 500 μM (Wanpen et al 2004). The treatment also decreased the levels of an anti-apoptotic protein bcl-2 and increased a pro-apoptotic protein bax (Shukla et al 2013;Wanpen et al 2007). Storch et al (2000) concluded that (RS)-salsolinol was toxic to human dopaminergic neuroblastoma SH-SY5Y cells by blocking the cellular energy supply via the inhibition of mitochondrial complex II activity but not complex I.…”
Section: Discussionmentioning
confidence: 97%
“…Oxidation of N -methylated derivatives into N -methylisoquinolinium ion augmented the potency to inhibit mitochondrial respiration and complex I (Morikawa et al 1998 ). Wanpen et al ( 2007 ) confirmed that mitochondrial complex I activity was significantly decreased, and reactive oxygen species were increased when SH-SY5Y cells were treated with racemic salsolinol. The treatment decreased the levels of the anti-apoptotic protein bcl-2 and increased pro-apoptotic protein bax, while enhancing the release of cytochrome c from mitochondria (Wanpen et al 2007 ).…”
Section: Salsolinol In Experimental Modelsmentioning
confidence: 97%
“…Wanpen et al ( 2007 ) confirmed that mitochondrial complex I activity was significantly decreased, and reactive oxygen species were increased when SH-SY5Y cells were treated with racemic salsolinol. The treatment decreased the levels of the anti-apoptotic protein bcl-2 and increased pro-apoptotic protein bax, while enhancing the release of cytochrome c from mitochondria (Wanpen et al 2007 ). Storch et al ( 2000 ) concluded that salsolinol was toxic to human dopaminergic neuroblastoma SH-SY5Y cells by blocking the cellular energy supply via the inhibition of mitochondrial complex II activity (succinate-Q reductase) but not that of complex I.…”
Section: Salsolinol In Experimental Modelsmentioning
confidence: 97%